Lorcaserin Administration has Pro-Ejaculatory Effects in Rats via 5-HT2C Receptors Activation: A Putative Pharmacologic Strategy to Delayed Ejaculation? - de Almeida Kiguti, Luiz Ricardo; Pacheco, Tainá Louise [UNESP]; Antunes, Edson; Kempinas, Wilma de Grava [UNESP] (Oxford University Press (OUP), 2020)
Background: Lorcaserin is an anti-obesity drug whose weight loss effect results from 5-hydroxytryptamin (5-HT)2C receptors activation. The 5-HT2C receptor was shown to participate in the physiological control of ejaculation, but no data addressing a putative effect of lorcaserin on ejaculation exist. Aim: To investigate the effects of lorcaserin in different in vitro and in vivo experimental models of ejaculation in rats. Methods: Contractile responses to lorcaserin in rat seminal emission organs in vitro (prostatic and epididymal vas deferens, cauda epididymis, and seminal vesicles), analysis of male rat copulatory behavior, and electromyographic recording of bulbospongiosus muscle in anesthetized animals were studied. Main Outcome Measures: The main outcome measures included in vitro contraction of seminal emission organs and evaluation of the male rat copulatory behavior. The male rat sexual behavior in terms of copulation latency, ejaculation latency, mount and intromission frequency, and ejaculation frequency of sexually experienced adult male rats with a receptive female were also recorded. Results: Lorcaserin (1.0 nM to 1.0 mM) had no significant effects on the in vitro contractility of seminal emission organs smooth muscle (cauda epididymis, vas deferens, and seminal vesicles). On the other hand, lorcaserin administration (0.3–1.0 mg/kg, intravenous) induced ejaculation in anesthetized rats, which was prevented by the 5-HT2C-selective antagonist SB 242084 (0.1 and 0.3 mg/kg, intravenous). Single-dose treatment of non-anesthetized male rats with lorcaserin (1.0, 4.0, or 10 mg/kg, per os) induced non-copulating ejaculations in sexually naïve rats. Lorcaserin also had pro-ejaculation effects by decreasing the ejaculation threshold of copulating rats by half. The pro-ejaculatory effects of lorcaserin were reversible as the ejaculation threshold of treated rats recovered after a 1-week washout period. Clinical Implications: Due to its reported clinical safety, repurposing lorcaserin for the treatment of delayed ejaculation may be suggested. Strengths & Limitations: The pro-ejaculatory effect of lorcaserin administration and the role of 5-HT2C were demonstrated in different experimental models of ejaculation in rats. The lack of studies in putative experimental models of delayed ejaculation is a limitation of this study. Conclusion: Our results demonstrate that the clinically approved 5-HT2C agonist lorcaserin is a strong facilitator of ejaculation in rats. de Almeida Kiguti LR, Pacheco TL, Antunes E, et al. Lorcaserin Administration has Pro-Ejaculatory Effects in Rats via 5-HT2C Receptors Activation: A Putative Pharmacologic Strategy to Delayed Ejaculation? J Sex Med 2020;17:1060–1071.
Keywords: Bulbospongiosus Muscle; Copulation; Epididymis; Seminal Vesicle; Vas Deferens